(untitled) (Research, Society and Development, 2022)
Objective: The purpose of the present study was to show information about the effects of probiotics on inflammatory and Renin Angiotensin System (RAS) balance, and their potential therapeutic role in the management of COVID-19. Methodology: This is a narrative literature review and the databases used were Google Scholar and Medline/Pubmed. Results: Some components of the intestinal microbiota, including Coprobacillus, Clostridium ramosum, Morganella morganii, and Streptococcus infantile were identified as positively correlated with the severity of the disease, while Faecalibacterium prausnitzii showed a negative correlation with SARS-CoV-2 infection. Probiotics emerge as a therapeutic alternative for the treatment of inflammatory conditions due to their effects on the maintenance of gastrointestinal integrity and repair properties. More specifically, probiotics from Bifidobacterium e Lactobacillus genus show benefits in the management of respiratory diseases and might enhance vaccine immunogenicity. Conclusion: The present study demonstrates the complementary therapeutic potential of probiotics in the treatment of respiratory infections, such as COVID-19. Beyond that, considering the diversity of probiotic strains, the evaluations already carried out and the data available in the literature, the present study points to the need for complementary studies to understand the mechanisms related to the effects of probiotics on COVID-19.